The Non-halogenated flame retardant handbook - Morgan, Alexander B.; Wilkie, Charles A., 1941- (Beverly, MA : Scrivener Publishing ; Hoboken, New Jersey : Wiley, 2014)
Due to the emphasis on replacing halogenated flame retardants with alternate technologies, this handbook contains in one place all of the current commercial non-halogenated flame retardant technologies, as well as experimental systems near commercialization. This book focuses on non-halogenated flame retardants in a holistic but practical manner. It starts with an overview of the regulations and customer perceptions driving non-halogenated flame retardant selection over older halogenated technologies. It then moves into separate chapters covering the known major classes of non-halo.
3.6 Reactive Resins/Thermoset Applications3.6.1 Production Processes for Glass Fibre Reinforced Polymer Composite; 3.6.1.1 Paste Production; 3.6.1.2 Hand Lamination/Hand-lay-up; 3.6.1.3 SMC and BMC; 3.6.1.4 Pultrusion; 3.6.1.5 RTM/RIM; 3.6.2 Formulation Principles; 3.6.3 Public Transport Applications of GFRP; 3.6.4 E & E Applications; 3.6.5 Construction and Industrial Applications; 3.7 Summary, Trends and Challenges; References; 4 Nitrogen-based Flame Retardants; 4.1 Introduction; 4.2 Main Types of Nitrogen-based Flame Retardants; 4.3 Ammonia-based Flame Retardants.
Includes bibliographical references and index.
4.3.1 Ammonium Polyphosphate.
Online resource; title from PDF title page (Wiley, viewed June 4, 2014).
Keywords: Fireproofing agents -- Handbooks, manuals, etc; Fire resistant plastics -- Handbooks, manuals, etc; Fire extinguishing agents; Fire resistant polymers; Nanostructured materials; Polymeric composites; TECHNOLOGY & ENGINEERING -- Environmental -- General; Fire resistant plastics; Fireproofing agents; Electronic books; Handbooks and manuals; Electronic books